STUDY ABOUT HALAL TOURISM DEVELOPMENT (CASE STUDY ON THE TOURISM INDUSTRY IN BANGKALAN, EAST JAVA) - Wispandono Moch; Faidal Faidal; Woro Utari; Rizdika Mardiana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Tourism development in the region must be based on planning, organizing, developing, and managing clear directions and local wisdom so that all the potential of a tourist destination can be optimally empowered to improve community welfare and local revenue (PAD). One of the most successful tourism development concepts today is related to the development of halal tourism which is carried out jointly between the community, government, and investors. The purpose of this study is focused on analyzing the problems and potentials of natural, historical, religious, and culinary tourism destinations in Bangkalan as a reference for managing sustainable tourism based on halal tourism that is suitable for Bangkalan district. This study uses a qualitative research approach. The use of a qualitative approach with the case study method is related to the aspect of understanding and reviewing the tourism development management process that can generate local revenue (PAD) in Bangkalan district. The results of this study indicate that in managing sustainable halal tourism by taking into account the problems and potential of tourist destinations that can be developed to increase PAD is through tripartite cooperation between the government, the community, and investors. The existence of this collaboration becomes a model of a sustainable tourism development strategy that is a hope for the government and society to improve the economy and economic activity. Keywords: Sustainable Tourism, Halal Tourism, Original Income, tripartite cooperation